How we die - Nuland, Sherwin B. (London : Vintage Books, 1997)
Presents a meditation and portrait of the experience of dying that elucidates the decisions that can be made to allow each person an understanding of death, as well as his or her own choice of death.
The strangled heart -- A valentine--and how it fails -- Three score and ten -- Doors to death of the aged -- Alzheimer's disease -- Murder and serenity -- Accidents, suicide, and euthanasia -- A story of AIDS -- The life of a virus and the death of a man -- The malevolence of cancer -- Hope and the cancer patient -- The lessons learned.
Includes index.
Originally published: New York : Knopf, 1994.
Keywords: Death; Death; Pastoral care